How children become invisible in child protection work: findings from research into day to day social work practice - Ferguson, Harry (Oxford University Press, 2016)
It is well known that in cases in which abused children have died, social workers and other professionals did not relate to them effectively—the phenomenon now known as the ‘invisible child’. Much less well understood is how often and why such invisibility occurs where there has not been a major inquiry or scandal and this paper draws on research which observed day-to-day encounters between social workers, children and families. In most of the practice, children were seen and related to but, in a small number of home visits, social workers were not child-focused. The paper provides a detailed analysis of those cases and shows how social workers were overcome by the emotional intensity of the work and complex interactions with angry, resistant parents and family friends. Workers were also affected by organisational culture, time limits on their work and insufficient support to enable them to contain their feelings and think clearly. The powerful impact of unbearable levels of complexity and anxiety on social workers requires much greater recognition. Sociological, psycho-dynamic and systemic theories are drawn upon to establish how workers need to be helped to think clearly about children and relate to them in the close, intimate ways that are required to keep them safe.